Smart wheelchair using android smartphone for physically disabled people - Mirin, Siti Nur Suhaila; Mohd Annuar, Khalil Azha; Yook, Chai Pui (International Journal of Engineering and Technology, 2018)
This paper describes the development of a smart wheelchair system with voice recognition and touch controlled using an embedded system. An android application is developed and installed on the android smartphone. The system is divided into two main modes: voice recognition mode and touch mode. For the voice recognition mode, elderlies or physically disabled people (users) can provide the voice input, for example, â€œgoâ€, â€œreverseâ€, â€œturn to the leftâ€, â€œturn to the rightâ€ and â€œstopâ€. The wheelchair will move according to the command given. For the touch mode, the user can select the specified direction displayed within the four quadrants on the screen of the android smartphone to control the wheelchair. An Arduino Uno is used to execute all commands. The MD30C motor driver and HC05 Bluetooth module are used in this system. This system is designed to save time and energy of the user.